Effect of the fragrance on the sensorial performance of cosmetic shampoos (2013)
Fragrances are a key factor when cosmetics are developed because of their crucial influence on the consumer acceptance. However, the development stages of the product are frequently focused on factors such as the cosmetic performance and the olfactory profile, overlooking the potential chemical interactions between the recipe ingredients and the fragrance ingredients like their consequences in terms of the product performance. As a contribution on this regard, this research evidences the incidence of different fragrances on the functional performance of cosmetic shampoos. The results reveal that the organic solvent included into the fragrance recipe could influence in significant way the behavior of polymeric raw materials which govern both the product viscosity and the product sensorial performance when in use tests are carried out.